Recent advances in proteolysis and peptide/protein separation by chromatographic strategies - Zhang, XiangMin (Sci China Chem, 2010)
This review gives a broad glance on the progress of recent advances on proteolysis and peptide/protein separation by chromatographic strategies in the past ten years, covering the main research in these areas especially in China. The reviewed research focused on enzymatic micro-reactors and peptide separation in bottom-up approaches, and protein and peptide separation in top-down approaches. The new enzymatic micro-reactor is able to accelerate proteolytic reaction rate from conventionally a couple of hours to a few seconds, and the multiple dimensional chromatographic-separation with various models or arrays could sufficiently separate the proteomic mixture. These advances have significantly promoted the research of protein/peptide separation and identification in proteomics.